1986
DOI: 10.1152/jappl.1986.61.4.1410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydration on plasma volume and endocrine responses to water immersion

Abstract: To determine the effect of hydration on the early osmotic and intravascular volume and endocrine responses to water immersion the hematocrit, hemoglobin, plasma renin activity (PRA), and plasma electrolyte, aldosterone (PA), and vasopressin (PVP) concentrations were measured during immersion following 24-h dehydration; these were compared with corresponding values following rapid rehydration. Six men and one woman (age 23-46 yr) underwent 45 min of standing immersion to the neck preceded by 45-min standing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…16 Tilting level and duration clearly influence the degree of thoracic blood volume, atrial diameter, and central venous pressure decrease in healthy young people, 17 with commensurate increase in plasma catecholamines, renin-angiotensinaldosterone, and occasionally vasopressin. 18 Our results demonstrate that orthostasis elicits stimulus-dependent ADM increase as part of a "quick humoral response," along with epinephrine and norepinephrine. Even at 30°HUT (sin, 0.5), the effects were significant within 3 minutes.…”
Section: Discussionmentioning
confidence: 60%
“…16 Tilting level and duration clearly influence the degree of thoracic blood volume, atrial diameter, and central venous pressure decrease in healthy young people, 17 with commensurate increase in plasma catecholamines, renin-angiotensinaldosterone, and occasionally vasopressin. 18 Our results demonstrate that orthostasis elicits stimulus-dependent ADM increase as part of a "quick humoral response," along with epinephrine and norepinephrine. Even at 30°HUT (sin, 0.5), the effects were significant within 3 minutes.…”
Section: Discussionmentioning
confidence: 60%
“…16 Harrison et al reported P-RA in the state of normal hydration is lower than under dehydration, and that increases in P-RA during HUT are attenuated following rehydration. 17 Our subjects were asked to take a light lunch on the day of HUT, but breakfast was not restricted and several patients took no lunch on the day of HUT. The extent of sodium loading and hydration status consequently differed between individuals according to their eating habits despite supplementation with saline (1 ml/min) during the HUT; this could influence the results.…”
Section: Effects Of Alcohol On P-avp and P-ra At Rest And During Hutmentioning
confidence: 99%
“…Immersion has been shown to significantly increase diuresis (Claybaugh et al 1986;Deuster et al 1989;Epstein 1978;Harrison et al 1986;Rochelle and Horvath 1978). Accompanying the increased urine production is an increased loss of sodium (Na) and potassium (K) ions (natriuresis and kaliuresis) (Epstein et al 1975;Epstein 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged immersion diuresis, either with or without supplemental water intake, produces significant plasma volume loss over a range of 8Z to 18% and whole body dehydration (Bmning et al 1972;Deuster et al 1989;Doubt et al 1988;Epstein 1978;Harrison et al 1986;Rochelle and Horvath 1978;Goforth, unpublished data). Dehydration (Buskirk et al 1958;Jacobs 1980), hypohydration (Caterisano et al 1988;Caldwell et al 1984), and plasma volume lois negatively affect work capacity (Coppin et al 1978;Craig and Cummings 1966;53itin 1964).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation